2022
DOI: 10.1038/s41598-022-08126-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, awareness, and treatment of depression among community-dwelling stroke survivors in Korea

Abstract: Post-stroke depression (PSD), a prevalent complication of stroke, causes poor outcomes. However, little is known about its prevalence and management among community-dwelling stroke survivors. Thus, we investigated the prevalence, awareness, and treatment of PSD in a community setting. A cross-sectional study was performed using representative data from the Korea National Health and Nutrition Surveys 2014, 2016, and 2018. A total of 11,122 participants aged ≥ 40 years were categorized, including 343 stroke surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Previous studies have also reported similar findings of inadequate awareness and knowledge regarding PSD treatment among stroke survivors, as well as their family caregivers. 26 27 Therefore, developing educational interventions for stroke survivors, family caregivers and healthcare professionals on PSD treatment options and engaging in patient-centred communication to dispel misconceptions were crucial to address the issue of low awareness of treatment risks and benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also reported similar findings of inadequate awareness and knowledge regarding PSD treatment among stroke survivors, as well as their family caregivers. 26 27 Therefore, developing educational interventions for stroke survivors, family caregivers and healthcare professionals on PSD treatment options and engaging in patient-centred communication to dispel misconceptions were crucial to address the issue of low awareness of treatment risks and benefits.…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy between the reported proportion of stroke survivors affected by clinically significant symptoms of depression and those who receive treatment is striking and raises questions about the validity of the approach most studies use to define depression (i.e., specific cut-points of various depression scales) or, alternatively, about the poor sensitivity of health professionals to identify stroke survivors with depression. A recent study of 343 stroke survivors living in Korea showed that less than half of those with depression were aware of their clinical status, and only 20% of these were receiving antidepressant treatment [9].…”
Section: Stroke and Depressionmentioning
confidence: 91%
“…A high percentage of stroke survivors develop clinical depression, with estimates ranging between 20 to 75% of patients [31,140,141], especially among females [141]. Although the pathophysiology of post-stroke depression is not completely understood, some contributing brain changes have been described.…”
Section: The Role Of Brain Ischemiamentioning
confidence: 99%